2012
DOI: 10.1590/s1415-47572012005000037
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among populations and accessions of the spineless peach palm from Pampa Hermosa landrace used in the heart-of-palm agribusiness in Brazil

Abstract: Although originally domesticated for its fruit, exploitation of the peach palm (Bactris gasipaes Kunth) in the production of gourmet heart-of-palm has also become an important activity, hence the need for improved material for large-scale production, on employing the Pampa Hermosa landrace as the seed source. In this study 11 microsatellite markers were used to evaluate genetic divergence among 96 elite plants representing four populations of spineless peach palm from the above cited source. Genetic variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“… Cole et al (2007) detected considerable inbreeding ( F = 0.105–0.210) in peach palm populations belonging to peasant and indigenous communities in northeastern Peru, confirming that traditional practice favors a certain level of biparental inbreeding, even though there is significant gene flow mediated by farmer seed sourcing ( Adin et al , 2004 ). Alves-Pereira et al (2012) found similar levels (0.156–0.210) within the Pampa Hermosa landrace with a larger sample. Generations of generally unconscious selection for yield will maintain productivity even as heterozigosity decreases due to inbreeding ( Hancock, 2004 ).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“… Cole et al (2007) detected considerable inbreeding ( F = 0.105–0.210) in peach palm populations belonging to peasant and indigenous communities in northeastern Peru, confirming that traditional practice favors a certain level of biparental inbreeding, even though there is significant gene flow mediated by farmer seed sourcing ( Adin et al , 2004 ). Alves-Pereira et al (2012) found similar levels (0.156–0.210) within the Pampa Hermosa landrace with a larger sample. Generations of generally unconscious selection for yield will maintain productivity even as heterozigosity decreases due to inbreeding ( Hancock, 2004 ).…”
Section: Introductionsupporting
confidence: 53%
“…The estimated total variance effective size ( N e ( v ) t ) of the population samples (maximum 30.6) of these three river basins in the Pampa Hermosa landrace is lower than what is considered acceptable for genetic conservation at the population level (minimum 50, Frankel and Soulé, 1981 ). However, the high gene flow among these populations ( Adin et al , 2004 ; Alves-Pereira et al. , 2012 ; and Rodrigues DP (2007) PhD Thesis, Universidade Federal do Amazonas, Manaus, AM, Brazil) suggests that conservation should be planned at the landrace level, where the estimated N e ( v ) = 86.8 is well above the minimum for short term conservation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations